MODIFIED D-GLUCOFURANOSE COMPUTATIONALLY SCREENING FOR INHIBITOR OF BREAST CANCER AND TRIPLE BREAST CANCER: CHEMICAL DESCRIPTOR, MOLECULAR DOCKING, MOLECULAR DYNAMICS AND QSAR - Kumer, Ajoy; Chakma, Unesco; Chandro, Akhel; Howlader, Debashis; Akash, Shopnil; Kobir, Md. Eleas; Hossain, Tomal; Matin, Mohammed M. (Journal of the Chilean Chemical Society, 2022)
Drug discovery and the process of new drug design have been formulated much easier in the past two decades by introducing and proliferation of combined physical and biochemical process from computing capabilities and computational approaches. Since the breast cancer is one of the life-threatening problems globally, and no effective prescription is still now invented or not available in the market or medical treatment. Although few is just touched on the market, but the remedy has consisted of severe side effects and low efficiency. Regarding that fact, the D-Glucofuranose and its derivative have been designed by the quantum calculation, molecular docking, ADMET and SAR analysis. For molecular docking, the cancer protease (3hb5) and triple-negative breast cancer protease (4pv5) are selected whereas the binding affinity is at ranging from -6.20 to -10.40 kcal/mol, and it is slightly lower than cancer protease (3hb5) for triple-negative breast cancer protease (4pv5). Our comprehensive study has shown that 03, 05, and 08 could be considered the potential drug comparison with standard. These three drugs completed all the criteria, including high binding energy, non-toxic, non-carcinogenic, and highly soluble in biological system.